ANALYSIS OF THE EFFECT OF EDUCATION FUNDS, HEALTH FUNDS, AND LABOR FUNDS ON REGIONAL INCOME IN SOUTH TANGERANG CITY PERIOD 2013 – 2018 - FIRDAUS BUDHY SAPUTRO (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This study aims to analyze the effect of education funds, health funds, and labor funds on regional income partially and simultaneously. The analysis uses panel data with multiple regression models or multiple regression. The data used in this study are secondary data obtained in ready-made form from www.djpk.depkeu.go.id and www.bps.go.id. The data obtained are data in annual form for each variable. The research period is data from 2013 to 2018. The results of this study indicate that the health fund variable has a partial effect on gross domestic product. While the variable education funding and employment absorption does not have a partial effect on gross domestic product. The results of simultaneous panel data regression, the results of the F test show that the three independent variables namely education funds, health funds and absorption of labor funds simultaneously influence the gross regional domestic product (GRDP).